Relation Between Quality of Transportation and Nano-Scale Air Pollution - Elif Cicek; Semra Ide; Cem Küçük; Oğuzhan Yorulmaz; Murat Vedat Yurttaş; Özge Zorlu Kaymak; Dilem Ergün (The Baltic Journal of Road and Bridge Engineering)
This study has two parts as determining traffic LOS and nanoscale analyses on the filters which can collect nanoparticle materials sourced by exhaust waste. Therefore, at first, determination of the traffic behaviour as the level of service (LOS) in Sıhhiye campus of Hacettepe University in Ankara was studied. Then, exhaust gas analysis by using facing masks was conducted for different parameters and these masks were used to collect and analyse exhaust on them. The parameters were determined as vehicle and fuel types, filter masks, sampling distances respect to exhaust source. The measurements and samplings were realized for the vehicles which are public cars and service minibuses which use different fuel types as petrol, eco-diesel and diesel. Additionally, 5 different filter types were used to analyse traffic behaviour as exhaust gas may affect human health. For this reason, different mask types with different specified parameters, which are using as face masks for health and a new type was prepared by Argiope lobata spider silk membrane, were also investigated in relation to the filtered exhaust gases. Measurements were made for three different distances as 30, 60 and 90 cm from exhaust pipe output and with a constant sampling time range of 3 min. Apart from the previously known microscopic and macroscopic analyses on exhaust gases, it was examined whether the exhaust outputs frequently spread nanoparticle waste or not by using SAXS analyses on samples. As a result of the study, relation with traffic conditions with clear transportation can be affirmed. Additionally, the study reported important outcomes, such as a new designed filter mask material, which prevents the nanoparticles waste material, the critical distance from the exhaust sources and the importance of different fuel usage.